PENGARUH SUHU YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP (SURVIVAL RATE) LARVA IKAN KARPER MAJALAYA (CYPRINUS SP): Influence of Different Temperature to Continuity of Life ( Survival of Rate) Fish Carp of Majalaya ( Cyprinus Sp) - Lalu Makrullah; Aryani Rahmawati; Luh Gede Sumahiradewi; Lalu Samsul Rizal (Yayasan Al-Amin Qalbu, 2023)
Intention of this research that is to know influence of different temperature to continuity of carp fish life of majalaya (Cyprinus sp) and to know best temperature to continuity of carp fish life of majalaya. Method which is used in this research is method